A rapid occultation event in NGC 3227. Issue 2 (6th September 2018) - Turner, T J; Reeves, J N; Braito, V; Lobban, A; Kraemer, S; Miller, L
ABSTRACT: NGC 3227 exhibits rapid flux and spectral variability in the X-ray band. To understand this behaviour, we conducted a coordinated observing campaign using 320 ks of XMM–Newton exposures together with 160 ks of overlapping NuSTAR observations, spanning a month. Here, we present a rapid variability event that occurs toward the end of the campaign. The spectral hardening event is accompanied by a change in the depth of an unresolved transition array (UTA), whose time-dependent behaviour is resolved using the RGS data. This UTA fingerprint allows us to identify this as a transit event, where a clump of gas having N_ H 5 × 10^22 atoms cm^-2, log ξ ∼ 2 occults 60 per cent of the continuum photons over the course of approximately a day. This occulting gas is likely associated with clouds in the inner broad-line region. An additional zone of gas with lower column and higher ionization, matches the outflow velocity of the variable zone, and may represent transmission through the cloud limb.